프로그램의 정보 보안을 위한 데이터 접근 제어 모델의 설계 및 구현 - 임현일(Hyun-il Lim) (디지털콘텐츠학회논문지, 2019)
정보화 시대에서 방대한 정보 및 데이터들을 효과적으로 관리하고 활용하는 것이 필요하며, 데이터 관리 기술은 다양한 응용 분야에서 중요한 부분을 차지하고 있다. 데이터 처리에서 중요한 보안 정보는 외부로 부터의 침임 및 유출로부터 효과적으로 관리할 수 있어야 하며 이런 정보를 보호할 수 있는 기술은 안전한 시스템 운용을 위해서 필수적이다. 접근 제어 모델은 데이터에 허가되지 않은 접근을 차단하고 중요 데이터를 안전하게 보호하기 위한 모델로 활용되고 있다. 본 논문에서는 프로그램에서 사용되는 데이터에 대해서 외부 유출 또는 허가되지 않은 접근으로부터 보호할 수 있는 데이터의 보안 등급을 정의하고, 외부의 접근으로부터 차단할 수 있는 데이터 보안 언어 및 접근 제어 모델을 설계한다. 본 논문에서 제안한 모델은 정의된 보안 데이터를 효과적으로 보호할 수 있음을 실험 결과를 통해 확인한다. In the information system, effective management and use of vast amounts of information data play important roles in various applications. To effectively manage information, secure information must be prevented from external intrusion or information leak. So, the technology for protecting secure information against unauthorized access is essential for a safe information system. Access control models can be used to secure data from unauthorized access and to protect against illegal access. This paper presents a data secure language and access control model that can define the security levels of data in a program and protect the data against unauthorized access. The proposed access control model can effectively manage data defined as secure information, and can improve information security of programs. Finally, the accuracy of the proposed model is evaluated through implementation and experiment. KCI Citation Count: 1